Studi Kuat Tekan Beton SCC dengan Variasi Fly Ash dan Sika Viscocrete pada Perendaman Air Laut - Gama Nurhickmah; Anggi Rahmad Zulfikar (Jurnal Sipil Terapan, 2025)
The durability of Self-Compacting Concrete (SCC) containing fly ash and Sika Viscocrete can be affected by exposure to seawater. This research investigates how seawater curing impacts the compressive strength of SCC modified with varying fly ash content and Sika Viscocrete admixture. The concrete mixtures were designed with 0% and 30% fly ash by cement weight and a constant 1% dosage of Sika Viscocrete. Compressive strength tests were conducted at 7, 14, and 28 days. The findings indicate that seawater curing has a notable effect on compressive strength, producing generally higher strength values than those cured in freshwater. Under freshwater conditions, strength increased steadily at 14 and 28 days, peaking at 54.1 MPa with 30% fly ash at 28 days. Conversely, the highest strength under seawater curing was achieved earlier, at 7 days, also with 30% fly ash, reaching 56.1 MPa. Overall, the optimum compressive strength was attained with a 30% fly ash mixture cured in seawater, suggesting this method enhances early-age strength in SCC.